2019
DOI: 10.17860/mersinefd.533593
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Türkçe Dersi Öğretim Programlarında Sözlük Kullanma Alışkanlığı Kazandırmaya Dair Tespitler

Abstract: Bu çalışmada, ortaokul Türkçe dersi öğretim programlarının sözlük kullanma alışkanlığı kazandırmaya yönelik özelliklerinin tespit edilmesi amaçlanmaktadır. Bu çalışmada, nitel araştırma yaklaşımı benimsenmiştir. Cumhuriyetten günümüze kadar hazırlanan (1924-2018) ilköğretim ikinci kademe Türkçe dersi öğretim programlarında tespit edilen; sözlüğe yönlendiren, sözlük kullanmayı telkin ve teşvik eden kazanımlar ile çalışma sınırlandırılmıştır. Araştırma verilerinin toplanmasında doküman incelemesi tekniği kullanı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
1
3
0
6
Order By: Relevance
“…Within the scope of the projects, it was found that activities such as reading activities, book clubs, drawing pictures, reading exam, drama, interview, book-telling, watching movies, panel, interview with the author, question-answer, writing, preparing board, commentary of a book and book presentation were performed. Out-of-school book activities are effective in having students gain reading habits (Acıyan, 2008;Karatay and Dilekçi, 2020a;Karatay and Dilekçi, 2020b;Maden and Maden, 2018). With regards to projects, extracurricular book activities may have positive effects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the scope of the projects, it was found that activities such as reading activities, book clubs, drawing pictures, reading exam, drama, interview, book-telling, watching movies, panel, interview with the author, question-answer, writing, preparing board, commentary of a book and book presentation were performed. Out-of-school book activities are effective in having students gain reading habits (Acıyan, 2008;Karatay and Dilekçi, 2020a;Karatay and Dilekçi, 2020b;Maden and Maden, 2018). With regards to projects, extracurricular book activities may have positive effects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Alan yazında okuma alışkanlığını geliştirmek için; sınıf kitaplığı oluşturma, öğrencilere ilgi ve seviyesine uygun kitapların verilmesi, okunan kitap üzerine panel, münazara gibi değerlendirme programların düzenlenmesi, beğenilen ve ilgi çekici kitapların öğrencilere tavsiye edilmesi, okuma saati, kitabın canlandırılması, okuma çemberi, sözlük oluşturma gibi teknikler kullanılabileceği belirtilmiştir (Karatay ve Dilekçi, 2020a;Karatay ve Dilekçi, 2020b;Maden ve Maden, 2018). Projeler kapsamında yapılan etkinliklere bakıldığında okuma etkinliği, kitap sohbeti, resim yapma, kitap sınavı, drama, yazar ile söyleşi, kitabı anlatma, film izleme, soru-cevap yapma, yazı yazma, pano hazırlama, kitap yorumlama, kitap seslendirme ve kitap sunumu gibi çalışmaların yapıldığı görülmektedir.…”
Section: Sonuç Ve Tartışmaunclassified
“…Therefore, this result is similar to the result of the study. In their study, Maden and Demir (2019) made some findings about gaining the habit of using a dictionary and suggested that attention should be paid to the use of school dictionaries (synonyms, antonyms, concepts) that are appropriate for the subject and level. Therefore, it can be said that the finding of this study is similar to the recommendation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Sözlük, yabancı dil eğitiminde, kelime öğretiminden başlanmak üzere, yazılış, dil yapıları, eş anlamlılık, zıt anlamlılık, yakın anlamlılık, eş dizimlilik ve telaffuz gibi birçok boyutuyla kullanılabilecek araçlardan biridir. Sözlük, diğer araçlarla birlikte, bilinçli ve eş güdümlü kullanıldığında öğrenicinin kelime hazinesinin gelişmesine yardımcı olur (Dönger, 2015;S. Maden ve Demir, 2019;Özbay ve Melanlıoğlu, 2013).…”
Section: Yabancılara Türkçe öğRetiminde Sözlüğün Yeriunclassified